(untitled) (Progressive Agriculture, 2021)
This study examined the utilization of crop residues in agrarian zone of Bangladesh. Two categories of respondent participated in this study, such as old conservational agriculture research or farmer group and new conservational agriculture research or farmer group. Data were analyzed using both descriptive and inferential statistics. Crops grown within the study area includes rice, wheat, jute, pulses, oilseeds, maize, vegetables etc. Result of analysis shows that crops residues were mainly used for feeding their livestock (67.30%), cooking fuel (63.46%) and organic manure (74.04%) on the farms in old conservational agriculture research sites, where in new conservational agriculture research sites was used for feeding their livestock (68.64%), cooking fuel (57.06%) and organic manure (61.86%). It can therefore be concluded that crop residue are used within the study area as cooking fuel, animal feed, use with cow dung boll, fired at field, reuse during next cultivation and organic manure on farms. Progressive Agriculture 31 (3): 164-177, 2020